(untitled) (Journal of Mathematical Modeling and Fractional Calculus, 2025)
Population growth is driving up energy demand, and burning fossil fuels accounts for a sizable amount of global energy production. Since this adds to the rise in greenhouse gas emissions, lowering energy sector emissions is essential to achieving climate change goals. In this research, three hybrid fractional operators are used to investigate carbon emissions from the power sector. A hy brid fractional operator is used to modify differential equations throughout time and space in order to create a mathematical model that describes the human population, energy consumption, and at mospheric carbon dioxide concentration. Compartmental models offer a mathematical framework for comprehending systems and forecasting outcomes, which makes them essential fgor comprehending real-world events. The effectiveness of these novel operators is supported by a number of analyses, and the Lipschitz condition ensures unique results. The order of the fractional derivative has a major impact on the dynamical process that is used to construct the non-integer order model.